Панцирные клещи (Oribatei) из гнезд мелких млекопитающих Донецкого Приазовья - Буланова-3ахваткина, Е.М.; Усова, 3.В.; Скляр, В.Е.; Ярошенко, Н.Н. (Вестник зоологии, 1974)
For 12 months (1967-1968) 210 nests of small mammals (Apodemus syiDaictis L.,.
Mus musculus L., Microtus arvalis P a H., Cricetulus migratorius P all., Sicista
all., Citellus pygameus P all., Sorex minutus L.) were investigated in the south of the
Donets region. 32117 mites are collected (31888 samples from nests and 229 samples from
hosts). Mites inhabit 96% nests (202). Out of 462 examined animals of the same species
the mites are found on 30 ones. Altogether 96 taxonomic units are identified in the nests
(81 species). One species from the genus Scheloribates B e r 1 proved to be new for
science.
Oribella pectinata (M i c h.) , Scheloribates semidesertus B.-Z., Oppia sp., Ramusellcz
sp., Oppia nova O u d m s., Ceratozetes cisalpinus B e r I. may be considered as mass species.